The neurofibromatosis type I messenger RNA undergoes base-modification RNA editing. - Skuse, G R (1996)
A functional mooring sequence, known to be required for apolipoprotein B (apoB) mRNA editing, exists in the mRNA encoding the neurofibromatosis type I (NF1) tumor suppressor. Editing of NF1 mRNA modifies cytidine in an arginine codon (CGA) at nucleotide 2914 to a uridine (UGA), creating an in frame translation stop codon. NF1 editing occurs in normal tissue but was several-fold higher in tumors. In vitro editing and transfection assays demonstrated that apoB and NF1 RNA editing will take place in both neural tumor and hepatoma cells. Unlike apoB, NF1 editing did not demonstrate dependence on rate-limiting quantities of APOBEC-1 (the apoB editing catalytic subunit) suggesting that different trans-acting factors may be involved in the two editing processes.